Fashion Prints in the Age of Louis XIV : Interpreting the Art of Elegance - Tetart-Vittu, Françoise; Rosenbaum, Sandra; Norberg, Kathryn, 1948- (Book collections on Project MUSE., 2014)
"Analyzing French fashion prints and what these images represent and reveal about the fashion and culture of the seventeenth-century"--